Seismic analysis of the massive β Cephei star 15 Canis Majoris. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Walczak, Przemysław; Handler, Gerald
Abstract: 15 Canis Majoris is a quite massive ( M 14 M⊙ ) main sequence pulsator of the β Cephei type. Recent photometric (Handler2014 ) and spectroscopic (Saesen & Briquet, priv. comm.) observations confirm four pulsational frequencies and indicate possible additional modes. We calculated models fitting two frequencies identified as radial and dipole modes. Our analysis indicates rather effective overshooting from the convective core as well as a strong dependence of the minimal required overshooting parameter (αov, min ) on the metallicity, Z (αov, min -2.5 Z). When incorporating the non-adiabatic f -parameter (Daszynśka-Daszkiewicz & Walczak2009 ), defined as the ratio of the bolometric flux changes to the radial displacement, significant differences between the opacity tables were obtained. The comparison of the models derived with different codes is also interesting. We used two evolutionary codes: Warsaw-New Jersey (Pamyatnykh et al. 1998 ) and MESA (Paxton et al. 2011 ) and some systematic differences were found.